IMPLEMENTASI GOOD GOVERNANCE DALAM PENGADAAN LANGSUNG ELEKTRONIK PADA BIDANG PEMBINAAN SEKOLAH DASAR DISDIKBUD KABUPATEN SERANG - Jali Gojali (Badan Perencanaan Pembangunan Daerah Provinsi Banten, 2022)
The ongoing manual direct procurement results in non-transparency of the process, doubtful accountability, limited public participation and will result in processes and outputs that are prone to fraud because they are not in accordance with applicable legal rules, and do not pay attention to the element of equality in it. This study aims to determine whether the implementation of Good Governance in direct electronic procurement policies in the Elementary School Development Sector is in accordance with the principles: transparency, competence, accountability, participation, the rule of law, and equality. This study uses qualitative methods, data collection through in-depth interviews with 12 informants, observations, and documentation. The results of research in the field of Elementary School Development explained that out of a total of 24 direct procurement packages, 23 packages (95%) were carried out electronically. The implementation of Good Governance in Electronic Direct Procurement has met the principles of transparency, competence, accountability, participation, the rule of law and equality. In particular, the principle of the rule of law policies regarding direct electronic procurement, both presidential regulation number 12 of 2021, government goods/service procurement policy agency regulations number 12 of 2021, as well as regent's circular letter number 027/2799/BPBJ-2021 are implemented properly in terms of factors communication, resources, dispositions, and the bureaucracy in it show that these policies support the creation of good governance. However, in terms of communication factors related to the mechanism of rules and policies, continuous socialization from the authorities is needed so that these mechanisms and policies can be implemented properly.